Not only cancer: the long non-coding RNA MALAT1 affects the repertoire of alternatively spliced transcripts and circular RNAs in multiple sclerosis. (19th December 2018) - Cardamone, Giulia; Paraboschi, Elvezia M; Soldà, Giulia; Cantoni, Claudia; Supino, Domenico; Piccio, Laura; Duga, Stefano; Asselta, Rosanna
Abstract: Long non-coding RNAs (lncRNAs) are post-transcriptional and epigenetic regulators, whose implication in neurodegenerative and autoimmune diseases remains poorly understood. We analyzed publicly available microarray data sets to identify dysregulated lncRNAs in multiple sclerosis (MS), a neuroinflammatory autoimmune disease. We found a consistent upregulation in MS of the lncRNA MALAT1 (2.7-fold increase; meta-analysis, P  = 1.3 × 10 −8 ; 190 cases, 182 controls), known to regulate alternative splicing (AS). We confirmed MALAT1 upregulation in two independent MS cohorts (1.5-fold increase; P  < 0.01; 59 cases, 50 controls). We hence performed MALAT1 overexpression/knockdown in cell lines, demonstrating that its modulation impacts on endogenous expression of splicing factors ( HNRNPF and HNRNPH1 ) and on AS of MS-associated genes ( IL7R and SP140 ). Minigene-based splicing assays upon MALAT1 modulation recapitulated IL7R and SP140 isoform unbalances observed in patients. RNA-sequencing of MALAT1 -knockdown Jurkat cells further highlighted MALAT1 role in splicing (approximately 1100 significantly-modulated AS events) and revealed its contribution to backsplicing (approximately 50 differentially expressed circular RNAs). Our study proposes a possible novel role for MALAT1 dysregulation and the consequent AS alteration in MS pathogenesis, based on anomalous splicing/backsplicing profiles of MS-relevant genes.